New Insight Into Visual Adaptation in the Mudskipper Cornea: From Morphology to the Cornea-Related COL8A2 Gene - Hu, Wenxian; Mu, Yuan; Lin, Feng; Li, Xu; Zhang, Jie (Frontiers in Ecology and Evolution, 2022)
Much research has focused on visual system evolution in bony fishes. The capacity of visual systems to perceive and respond to external signals is integral to evolutionary success. However, integrated research on the mechanisms of adaptive evolution based on corneal structure and related genes remains limited. In this study, scanning electron microscopy (SEM) was used to assess the microstructure and adaptation of corneal epithelial cells. Then, the evolution of the cornea-related COL8A2 gene was investigated. We found various projections (microridges, microplicae, microholes, and microvilli) on the corneal epithelial cells of amphibious mudskippers. Compared with those of fully aquatic fishes, these microstructures were considered adaptations to the variable environments experienced by amphibious mudskippers, as they can resist dryness in terrestrial environments and infection in aquatic environments. Moreover, strong purifying selection was detected for COL8A2. In addition, some specific amino acid substitution sites were also identified in the COL8A2 sequence in mudskippers. Interestingly, the evolutionary rate of the COL8A2 gene was significantly and positively correlated with maximum diving depth in our dataset. Specifically, with increasing diving depth, the evolutionary rate of the COL8A2 gene seemed to gradually accelerate. The results indicated that the cornea of bony fishes has evolved through adaptation to cope with the different diving depths encountered during the evolutionary process, with the corneal evolution of the amphibious mudskipper group showing a unique pattern.